Genocias ir rezistencija Nr. 18(2) - Grigorian, Vahagn; ze, Kaspars; Olechnovič, Dmitrij; Juodis, Darius; Kšanytė, Raminta; Vyšniauskas, Arūnas; Ūsaitė, Kristina; Vasiliauskienė, Aldona (Genocidas ir rezistencija, 2005)
Pilnas leidinys (nuskenuota popierinė versija)